Cultivares de Milho Ensiladas em Diferentes Estádios de Maturidade - Vilela, Hélio Henrique (2006)
This research was conducted at the experimental farm of the José do Rosário Vellano University - UNIFENAS in Alfenas State of Minas Gerais Brazil during the 2005-2006 agricultural year with the purpose of evaluating the agronomic characteristics of corn cultivars the bromatololic aspects of their silages and dry matter intake The statistical design was in randomized blocks with four treatments and four replicates in the manner of portions subdivided with time (split plot in time) The portions comprised the treatments (cultivars) and the subportions consisted of the stages of maturity (SM) for ensiling the plants The cultivars used were Geneze 2004 (GNZ 2004) Agroceres 1051 (AG1051) Pioneer 30S40 (P30S40) and Pioneer 30F90 (P30F90) ensiled at the following stages of physiologic maturity of the grains no milk line (NML) reduction of the milk line in 1/3 of the grain (1/3 ML) 1/2 of the grain (1/2 ML) 2/3 of the grain (2/3 ML) and formation of black layer (BL) Both the lowest plant height (2,47 m) and ear insertion (1,27 m) values were observed in GNZ 2004 Cultivars P30S40 and P30F90 showed the highest plant height (2,66 and 2,73 m respectively) The highest percentage of laying plants (3,61%/ha) was observed in cultivar P30F90 The DM content increased simultaneously with the evolution physiological development of the corn plant and the highest average DM content occurred in grains with BL (44,78%) Most cultivars ensiled with the grains in 1/2 LL showed DM contents (35,79%) more appropriate for ensiling The DM productivity ranged from 15,07 t/ha (AG1051) to 24,75 t/ha (P30S40) The highest grain yield values were observed in the SM of 2/3 LL (9,65 t/ha) and BL (9,88 t/ha) The percentage of DM of the silages ranged from 26,53% in cultivar P30S40 harvested with the grains NML to 45,02% in cultivar GNZ2004 harvested with the grains showing BL and increased with the SM of the corn plant The largest losses of effluents were observed in the silages of cultiva r AG1051 (17,84 kg/t NM) and P30S40 (18,14 kg/t NM), with grains NML There were no losses from the SM 1/2 ML onwards As the SM do the corn progressed there was an increase in pH values ranging from 3,68 in cultiva r GNZ2004 harvested in the SM of BL, to 3,38 in cultiva r P30S40 harvested in the 1/3 ML The SM influenced the percentage of crude protein (CP) of the silages which ranged from 10,69% to 8,06% respectively in the silages NML and BL The percentage of NDF varied from 41,93% in the viii silage of cultivar P30F90 NML to 58,79% in cultivar GNZ 2004 when the grains showed BL The variation in the percentage of ADF ranged from 22,88% in the silage of cultivar P30F90 NML to 31,57% in cultiva r P30S40 when the grains showed BL The percentage of lignin was influenced by the cultivars and was higher in the silages of cultivar P30S40 (5,44%) The percentage of ashes was influenced by the SM varying from 2,95% in BL to 3,91% with the grains in 1/3 ML The IVDMD was influenced by the cultivars and SM ranging from 51,11% to 69,84% but in general cultiva r P30F90 showed higher IVDMD (64,53%)The best IVDMD was observed with the grains in 1/2 LL (66,56%) After that SM its values decreased With regard to DM intake there was no influence of either SM or cultivars with an average of 104,30g/kg PM or 5,22% of live weight It was concluded that cultivars GNZ 2004 AG1051 and P30F90 are more suitable for the production of silage and that the best stage of maturity for ensiling was when the grains showed reduction of the milk line in half of the grain (1/2 LL) the stage of maturity of the corn plant for ensiling had no influence on DM intake